Understanding The Role Of Government Policies In Shaping Higher Education Opportunities For Pakistani Students From Diverse Backgrounds - Dr. Shakeel Ahmed , Muhammad Fayaz (PhD) , Dr. Syeda Aysha , Dr .Ausima Sultan , Dr. Uzma Ahmad , Zubair Hussain , Kashif Lodhi (Migration Letters, 2024)
The study examines the influence of government policies on the availability of higher education for students from different socio-economic backgrounds in Pakistan. The introduction highlights the significance of inclusive education policies in advancing equal chances for higher education, particularly in a nation marked by socio-economic disparities. This study employs a mixed-methods research methodology, which combines quantitative analysis of educational data with qualitative interviews conducted with policymakers, educators, and students. Data gathering involves the examination of enrollment data, policy documents, and the administration of semi-structured interviews to acquire comprehensive insights. The data analysis reveals the impact of affirmative action legislation, scholarship programs, and regional development initiatives on the availability of higher education. Statistical tools are used to identify patterns and inconsistencies, whereas theme analysis is performed to interpret qualitative data. The findings indicate that while many measures have succ[1]essfully increased enrollment among marginalized groups, there are still significant barriers, including regional differences and insufficient financial resources. The result highlights the significance of developing comprehensive and well-funded strategies to tackle the educational disparity. Proposed recommendations include expanding scholarship programs, enhancing infrastructure in underdeveloped regions, and fostering public-private partnerships to support educational initiatives. This study offers a significant contribution to the discourse on educational equity and presents practical suggestions for policymakers to enhance the availability of higher education to all students in Pakistan.